Synthesis, electrical and photo-sensing characteristics of the Al/(PCBM/NiO: ZnO)/p-Si nanocomposite structures - Demirezen, S.; Cetinkaya, H. G.; Kara, M.; Yakuphanoğlu, Fahrettin; Altindal, S. (Elsevier Science Sa, 2021)
In this study, metal-oxide (NiO:ZnO) nanocomposites mixed with different weight-percentages (2, 10, 20 % NiO) content were coated on the p-Si wafer via spin-coating method. The optical and electrical features of the Al/(PCBM/NiO:ZnO)/p-Si structures/diodes were investigated and compared via currentvoltage/time (I-V/t) and capacitance/conductance-voltage-frequency (C/G-V-f) characteristics in dark and various illumination intensities (20, 40, 60, 80, 100 mW/cm(2)) at room temperature. Main electrical parameters of them such as ideality factor (n), barrier height (Phi(b)), rectification ratio (RR = I-F/I-R) and series resistance (R-s) were calculated for each percentage (2, 10, and 20 % NiO). Experimental results show that the best percentages of NiO is 20 % in respect of high value of RR and low Rs, but the value of n increases with increasing in percentages. The transient photocurrent increases with increasing illumination level. The slope (m) of the double-logarithmic I-ph -P plots were found as 0.67, 0.87 and 0.82, respectively, and these slopes confirmed that these nanocomposites exhibit photoconduction behaviour and hence Al/(PCBM/NiO:ZnO)/p-Si structure can be used a photo device/sensor. The observed changes in the I with illumination, C and G with frequency are the results of interface states (N-ss) located at (PCBM/NiO:ZnO)/p-Si interface and so reorder and restructure of them under illumination, bias voltage, and frequency. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Al/(PCBM/NiO:ZnO)/p-Si; Structures/diodes; Photo-response characteristics; Impedance spectroscopy method; Anomalous peak in the forward bias C-V plots